Fat Content, Water Content, Protein Content, and Antioxidant toward Edamame Tempeh (Glycine max (L) Merrill) with Different Types of Packaging - Nova Damayanti Kurniawan; Bhakti Etza Setiani; Bambang Dwiloka (Program Studi Teknologi Pangan, 2019)
The use of beans in Indonesia is very diverse, except for local edamame beans that have been widely grown in Indonesia. Edamame beans contain nutrients that are good for the body and a large amount of production but have not been balanced with large uses, such as processing into tempeh. Although tempeh has been widely circulated in Indonesia, but the tempeh from edamame beans is not known to the public even though it contains good nutrition for the body. The purpose of the study was to determine the effect of different types of packaging on fat content, water content, protein content, and antioxidants of edamame bean tempeh. Edamame bean tempe is made from locally edamame beans fermented using Aspergillus oligosporus mold. This research was conducted with 4 treatments and 5 replications with the treatment of various types of packaging namely T1 PE plastic packaging, T2 banana leaf packaging, T3 teak leaf packaging, and T4 aluminum foil packaging. This study used raw materials of local edamame beans, starter molds of Aspergillus oligosporus, PE plastic, banana leaves, teak leaves, and aluminum foil. The results obtained are the difference in packaging only gives a significant effect on water content, and does not have a significant effect on fat and protein levels. The highest antioxidant content was found in plastic packaging edamame tempeh, which was 86.60% and the lowest was in aluminum foil tempe edamame which was 70.90%.